Видовой состав и генетическая вариабельность бактериальных симбионтов тлей фауны Беларуси - Воронова, Н.В.; Сироткина, Д.П. (Фактори експериментальної еволюції організмів, 2015)
Aims. Symbiotic bacteria are of interest to biotechnology as potential tool for pest management. The aim of the study was to research the occurrence and diversity of secondary symbionts of specifi c genera in different species of aphids from Belarus. Methods. Biodiversity of bacterial symbionts was studied by PCR with genus-specifi ed primers. Genetic diversity was revealed with methods of bioinformatics. Results. The research showed that aphids of Belarusian fauna possess a wide range of symbiotic microorganisms. Among secondary symbionts of Belarusian aphids Rickettsia and Spiroplasma have almost 100 % frequency of occurrence despite the fact in literature they are considered as rare. Degree of the phylogenetic homogeneity of 16S rRNA and gltA genes in symbiotic rickettsia has been studied. It is shown that both the mean and the maximum interspecifi c genetic distances of 16S rRNA gene in pathogenic rickettsia have been signifi cantly lower than in symbiotic ones. Phylogenetic analysis of symbiotic rickettsia, based on 16S rRNA and gltA genes, has shown the existence of 4 separate clusters with high bootstrap value. Conclusions. The obtained data show possible existence of at least four different species of symbiotic bacteria in Rickettsia genus. Keywords: aphids, symbiotic bacteria, Rickettsia, PCR markers.